ЎҚУВЧИЛАРНИ ОИЛАВИЙ ҲАЁТГА ТАЙЁРЛАШДА ПСИХОЛОГИК - ИЖТИМОИЙ МУАММОЛАР - Сулетбаева, Э.С. (SCIENCE and SOCIETY, 2018)
The article deals with the training of learners for family life, psychological features of this problem, skills of family relationship and the rights and responsibility of every member of the family.
Keywords: жамият; инсоният; психология; оила; физиология; акселерация; ижтимоий функция; шахс; никоҳ